Pelatihan Pemanfaatan Artificial Intelligence Based Platform Sebagai Media Pembelajaran Interaktif bagi Guru Pesentren - Moh. Ridhoi (Universitas Negeri Malang, 2024)
This community service activity aims to enhance the quality of teaching for teachers at Ma’had Al Furqon Al Islami Gresik through training on utilizing Artificial Intelligence (AI)-based platforms in the development of interactive learning media. The rapid advancement of technology, particularly AI, offers innovative opportunities to create engaging and effective educational content. However, the lack of digital skills among many teachers often poses a barrier to its implementation. The program includes workshops and hands-on sessions focused on using AI-based tools to support learning in Islamic boarding schools (pesantren). Through a service-learning approach, teachers are provided with step-by-step guidance to integrate AI tools into their instructional design. The results of the activity indicate a significant improvement (31.15 points) in teachers' ability to understand the material presented, as evidenced by pre- and post-training evaluations. Participants also reported increased confidence in adopting technology to enhance student engagement and learning outcomes. This initiative demonstrates the potential of AI in bridging the gap between traditional teaching methods and modern educational needs, paving the way for more dynamic and student-centered learning environments.